(untitled) (Medico Legal Update, 2019)
We examine a case involving a 34-year-old man who died of complications following the self-inoculation of Paraquat for suicidal purposes. During the crime scene investigation were seized all the paraphernalia were analyzed and were positive for Paraquat. At the autopsy were found an area of hemorrhagic infiltration on the inside face of the abdominal wall, in correspondence of the right peri-umbilical region, following the self-inoculation of the Paraquat performed. The aspects of greatest interest of the particular case under examination have been analyzed. In particular, we have taken into consideration the biochemical and toxicological aspects of Paraquat and the medico-legal problems related to the inoculation of the compound.